Interação entre o brometo de piridostigmina e o desbalanço superóxido-peróxido de hidrogênio na cito-genotoxicidade de células neurais e imunes mononucleares - Azzolin, Verônica Farina (2018)
Pyridostigmine bromide (PB) is a reversible acetylcholinesterase inhibitor (AChE), and the first line of symptoms associated with neuromuscular junction disorders (JNM) and has been used prophylactically in the Persian Gulf War (GWI), for prevention of post-traumatic stress, exposure to heat and pesticides. The role of PB in relation to GWI disease, which includes symptoms such as fatigue, cognitive and musculoskeletal dysfunction, is still controversial. Since it is used alone it does not appear to present intense toxic effects, however associated to other drugs and chemical agents it becomes genotoxic and inducer of apoptosis in animals. Therefore, the objective of this study was to evaluate the interaction between PB and superoxide-hydrogen peroxide (S-HP) imbalance in the cytogenotoxicity of neural and mononuclear immune cells. Three experimental designs were conducted. The first study aimed to evaluate the effect of CP on cytotoxicity and genotoxicity in SHSY-5Y neural cells. An in vitro investigation using human neural cells (SHSY-5Y) was performed. Cells were exposed to PB in different concentrations, based on the plasma drug concentration for the treatment of Myasthenia Gravis MG (40 ng / mL). The concentration curve of the drug showed an inhibition of AChE activity. However, this effect was transient and did not involve the regulation of AChE gene expression. In general, PB did not trigger oxidative stress except at the highest concentration (80 ng/mL), protein damage and DNA damage were detected. Genotoxic effects were confirmed by increased expression of p53 and DNA methyltransferase 1 (DNMT1) genes, which are associated with cellular DNA repair. The concentration of 40 ng/mL, which is the minimal therapeutic dose, showed a less intense cytotoxic effect, promoting a greater cell proliferation and mitochondrial activity compared to the untreated group. These effects were corroborated by increased telomerase gene expression. Two other protocols were conducted to evaluate the genetic influence associated with the basal oxidative imbalance of S-HP triggered by the unique nucleotide polymorphism of the enzyme superoxide dismutase 2 (Val16Ala-SOD2 SNP, rs4880). The VV genotype presents higher levels of basal superoxide (O2 -), whereas AA exhibits higher levels of basal hydrogen peroxide (H2O2) when compared to that of the AV genotype. Therefore, the objective was to evaluate whether the Val16Ala-SOD2 polymorphism could alter the cytotoxic effects triggered by different concentrations of PB in peripheral blood mononuclear cells (PBMCs). PBMCs were obtained from volunteers with different genotypes of SOD2. Protein levels and gene expression of antioxidant enzymes, apoptotic markers (Bax, Bcl-2, caspases 3 and 8) and DNMT1 were evaluated in 24-hours cultures. In general, PB increased the gene expression of antioxidant enzymes and triggered apoptotic events in AA genotype cells. AA PBMCs are shown to be more sensitive to PB exposure, resulting in increased AChE inhibition, cell death, protein carbonylation and DNA damage as analyzed by the comet assay. In contrast, PB demonstrated cyto-genoprotective effects on V allele cells. These results suggest that genetic factors that increase the release of H2O2 may affect the efficiency and safety of PB. Finally, the third study aimed to evaluate in vitro the interaction between the pharmacological imbalance S-HP associated with PB in SHSY-5Y neural cells. An S-HP unbalance pharmacological protocol was developed to obtain cells similar to the AA-like genotype, presenting high levels of H2O2, and cells similar to the VV-like genotype, presenting higher levels of O2-. The results showed that the interaction between PB-associated S-HP imbalance decreased cell viability, increased levels of DNA damage in AA-like cells. Analysis of the gene expression and protein modulation of BAX, BCl-2, caspase 3 and 8 suggest that the cytotoxic effect on neural cells does not involve intrinsic or extrinsic apoptosis, suggesting the occurrence of other processes in cell death. VV-like cells had higher AChE activity than the equilibrated cells, and less efficacy in the inhibition of this enzyme by exposure to PB. Therefore, the interaction between the S-HP imbalance in association with PB may have some role in the development of GWI disease and in the occurrence of adverse effects in some patients who use it for the treatment of MG. In summary, despite the methodological limitations related to the in vitro studies, the results set confirmed that PB alone in neural cells does not cause extensive toxicity, however, when this is associated with S-HP oxidative imbalance in neural and peripheral cells can cause toxicity.